Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline Untuk Meningkatkan Self-Regulated Learning - Indi Zahrotul Hafidha; Nur Fauziyah; Sri Suryanti (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to: (1) produce a product in the form of appropriate and effective interactive learning media, (2) increase students' self-regulated learning. The subjects of this study were 30 students of class VII D UPT SMP Negeri 15 Gresik. This type of research is RnD and uses a 4D development model which includes define, design, development, and disseminate stages. The results showed: (1) the validation results obtained from the assessment by media experts and material experts were in the very appropriate category, and the effectiveness of the media was in the very positive category, (2) the level of self-regulated learning of students increased by 45% after learning. using interactive learning media based on the articulate storyline that has been developed. Thus, interactive learning media based on articulate storylines to improve self-regulated learning can be utilized to support the learning process.